Triumphing Over the Body: Body Fantasies and Their Protective Functions - Vissing, Helena (Journal of the Motherhood Initiative for Research and Community Involvement, 2015)
Pregnancy, birth, and motherhood exert tremendous pressure on all of a woman’s boundaries: physical, mental, emotional, spiritual, and social. In this article, I will discuss psychological boundary functions in relation to reproduction from psychoanalytic perspectives with a somatic focus. Reproductive functions pose special challenges for female boundary development. As the boundary transgressions of motherhood exert unique psychosomatic pressure, anxieties about loss and vulnerability are elicited, requiring the development of psychological defenses. I analyze two narratives in Western mainstream culture: The Supermodel Mother and Orgasmic Birth. The Supermodel Mother is untouched by the vulnerabilities connected to pregnancy, childbirth, and motherhood. This narrative is formed in mainstream media through preoccupation with celebrity pregnancy. Orgasmic Birth is cultivated in home birth movements, where the notion of a more truthful childbirth is elevated to an ecstatic and spiritual event of female self-realization. I will argue that these narratives are illusory solutions to the boundary challenge of reproduction and that they serve to protect against body anxieties through idealization. They are narratives namely about the body because they serve to protect against pre-verbal material from an unconscious relational realm that is not available for verbalization. The protective function of these fantasies lies in their contribution to a feeling of triumph over the body.